Jejak Relasi Kekhalifahan Islam di Tatar Sunda - Dhaiman, Arif Noor; Wirahadi, Wirahadi (Civilization Research: Journal of Islamic Studies, 2023)
This research is motivated by the obscured and buried history of Islamic caliphate relations in Sundanese Tatar. The purpose of this research is to find traces of Islamic caliphate relations in the Sundanese region. This research uses a qualitative approach and descriptive method. Based on the results of the research, Islamization in Sundanese Tatar is closely related to the preaching of Islam in the early era of the Companions and Tabi'in, which was famous for various futuhat led by the Caliphs. During the Abbasid Caliphate, there was a cultural relationship between the Caliphate and Islamization in Sunda.  During the Uthmanid Caliphate, there was a structural relationship with evidence of the title of Sultan from the Uthmanid Caliphate through the Sharif of Makkah as the guardian of the Caliphate, indicating the delegation of imarah 'ammah 'ala al-bilad to the Sultans to represent the Caliph in implementing Islamic Sharia and implementing Ri`ayah ash-Syu`un (managing the affairs) of the Muslims in their territory. This is because one of the functions of the Caliphate is to spread Islam to various countries, both through Da'wah and Jihad.